2015
DOI: 10.7904/2068-4738-vi(11)-23
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Spring Field Pea Genotypes

Abstract: Abstract. An analysis was carried out during 2011-2013 on eight field pea genotypes. On the basis of the obtained results, the following conclusions may be drawn and used for further research on the quantitative traits on forage pea and its application in breeding and the development of new varieties: Analysis of variance showed significant differences among genotypes for all traits. The results of coefficient of variation analysis showed that the genotypic coefficient of variation was higher than the phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
4
1
0
Order By: Relevance
“…It determines the amount of genetic variance to total phenotypic variance. Similar results for different characters have also been reported by Kosev et al, (2015). Genetic advance a measure of genetic gain under selection as per cent of population mean was low to high for various characters studied in the present experiment.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It determines the amount of genetic variance to total phenotypic variance. Similar results for different characters have also been reported by Kosev et al, (2015). Genetic advance a measure of genetic gain under selection as per cent of population mean was low to high for various characters studied in the present experiment.…”
Section: Resultssupporting
confidence: 91%
“…These results also supported with the findings of Saxesena et al, (2014) Similarly, the genotypic coefficients of variation (GCV) were high for plant height, pod yield per plant, pod yield per plot, number of pods per plant, number of cluster per plant, number of branch per plant, 50% germination and internode length whereas, moderate genotypic coefficients of variation (GCV) were recorded for, harvest index number of branch per plant, 100 seed weight, days to 50 % flowering, number of node per plant, dry matter content, pod length, days to maturity shelling percentage and 100 seed weight. Similar results for different characters have also been reported by Kosev et al, (2015).…”
Section: Resultssupporting
confidence: 90%
“…The above finding revealed the presence of substantial amount of genetic variability for the traits, which exhibited high magnitudes as well as less influence of environment on the expression of concerned traits. Similar results for different characters have also been reported by Saxesena et al, (2014); Katiyar et al, (2014); Ahmad et al, (2014); Kosev, (2015); Patel, 2017 andSahoo, 2018. Day to first flower opening, days to fifty per cent flowering, hundred seed weight, harvest index, total sugar, non-reducing suagr and ash exhibited moderate genotypic and phenotypic coefficient variation in both of environments except number of seed per pod and protein content. Mishra (2014), Jeberson et al, (2016) and Sahoo, (2018) also reported similar result.…”
Section: Phenotypic and Genotypic Coefficient Of Variationsupporting
confidence: 88%
“…High The above finding for high GCV and PCV revealed the presence of substantial amount of genetic variability for the traits, which exhibited high magnitudes as well as less influence of environment on the expression of concerned traits. Similar results for different characters have also been reported by Saxena et al [20]; Katiyar et al [21]; Ahmad et al [22]; Kosev [23]; Patel [17] and Sahoo [5]. Day to first flowering node, number of seed/pods , hundred seed weight (gm), harvest index and days to flower initiation exhibited moderate genotypic and phenotypic coefficient variation in all of the environments except.…”
Section: Environment-isupporting
confidence: 87%